Preparation method of all-inorganic perovskite quantum dot flexible interdigital back contact solar cell
By using all-inorganic perovskite quantum dot films and interdigital back contact solar cell structures on the flexible film, the problem of poor toughness of traditional flexible solar cell electrodes and polycrystalline films is solved, and high-efficiency photoelectric conversion and high-flexible perovskite quantum dot flexible interdigital back contact solar cell is achieved.
Patent Information
- Application Number
- CN202410195304.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-22
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The electrodes and polycrystalline films of traditional flexible solar cells have poor toughness, which limits the flexibility of the interdigital contact battery.
The perovskite quantum dot film and the contact solar cell structure of the back of the finger are used to prepare the perovskite quantum dot layer on the flexible film through ultrasonic spraying technology, and combined with the pressure-sensitive packaging glue to form a device with high flexibility and high efficiency photoelectric conversion.
It realizes the efficient photon conversion efficiency of perovskite quantum dot flexible interdigital contact solar cells, with high flexibility and low cost, suitable for large-scale production.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of quantum dot photovoltaic device applications, and in particular to a preparation method for combining all-inorganic perovskite quantum dots with interdigitated back contact cells. Background Art
[0002] As a zero-dimensional semiconductor optoelectronic material with a size within the nanometer scale, perovskite quantum dots have many advantages, such as high quantum fluorescence yield and adjustable optical band gap in the entire visible spectrum. Therefore, compared with traditional quantum dot materials, perovskite quantum dots have great application potential in optoelectronic devices such as solar cells and light-emitting diodes. Secondly, after the preparation of perovskite quantum dots, there is no need to complete the crystallization film formation process through thermal annealing. Compared with traditional polycrystalline perovskite materials, perovskite quantum dots are more suitable for low-temperature preparation of flexible devices.
[0003] Traditional vertical structure flexible solar cells use transparent conductive oxide films as electrodes, but such conductive films have disadvantages such as high preparation cost, weaker conductivity than metals, poor permeability and flexibility, which are not conducive to their application in flexible solar cells.
[0004] The PN junction and metal contact of the interdigitated back contact solar cell are both located on the back of the solar cell. This design avoids the appearance of metal grid electrode and welding electrode interconnection strips on the front surface, so that the front surface is not partially blocked by the metal. The interdigitated back contact solar cell avoids the obstruction of the front surface to the greatest extent by arranging the PN junction and metal contact on the back, improves the photoelectric conversion efficiency, and has the advantages of compact structure and beautiful appearance. The existing interdigitated back contact cells are mainly made of crystalline silicon materials, but defects such as poor plasticity of thin films made of crystalline silicon materials or other polycrystalline materials limit the development of flexible interdigitated back contact cells. Summary of the invention
[0005] The purpose of the present invention is to solve the above problems by taking advantage of the structure of perovskite quantum dots and interdigitated back contact solar cells to prepare perovskite quantum dot flexible interdigitated back contact solar cells. Perovskite quantum dot films have better toughness than polycrystalline films, and low-temperature preparation conditions are more suitable for flexible solar cells. The present invention aims to solve the problem of poor toughness of traditional flexible solar cell electrodes and polycrystalline films by taking advantage of the interdigitated back contact cell structure and perovskite quantum dot films.
[0006] Technical solution of the present invention: The present invention provides a device of an all-inorganic perovskite quantum dot flexible interdigitated back-contact solar cell, which combines the advantages of the all-inorganic perovskite quantum dot film and the interdigitated back-contact solar cell structure to solve the problem that traditional interdigitated back-contact solar cells cannot be flexibly applied on a large scale.
[0007] The present invention provides a method for preparing a device of an all-inorganic perovskite quantum dot flexible interdigitated back-contact solar cell, the method being as follows: (1) preparing an interdigitated metal electrode layer on a flexible film (polyethylene terephthalate flexible film) with a thickness of 120 nm; (2) spraying an electron transport layer and a hole transport layer on the metal electrode layer using ultrasonic spraying technology; (3) spraying a perovskite quantum dot layer on the electron transport layer and the hole layer using ultrasonic spraying technology, the quantum dot layer having a thickness of 80 nm and a size distribution of 5-15 nm; (4) preparing a layer of pressure-sensitive encapsulation adhesive on the perovskite quantum dot layer, the encapsulation adhesive having a main component of a tackifying resin.
[0008] Working principle of the present invention: The structure of the present invention is based on an interdigitated back contact battery structure. Since the electrodes, electron transport layer and hole transport layer in the interdigitated back contact structure are integrated on the same side, electrons and holes can be collected and transported on the same side of the back surface. Under illumination, photogenerated carriers are generated in the perovskite quantum dot layer, and then electrons and holes are transported through the tin dioxide electron transport layer and the nickel oxide hole transport layer, respectively, and finally collected by the positive and negative electrode regions corresponding to the interdigitated electrodes, respectively. Such a design can reduce the recombination of carriers inside the battery, improve the effective collection of carriers, and avoid the shortcomings of traditional transparent conductive oxide films.
[0009] The beneficial effects of the present invention are as follows: a device of an all-inorganic perovskite quantum dot flexible interdigitated back-contact solar cell, which relies on the high flexibility of the quantum dot film and the advantages of the interdigitated back-contact battery structure to maximize the photon conversion efficiency and demonstrate the advantages of the perovskite quantum dot flexible interdigitated back-contact solar cell; the perovskite quantum dot film can be deposited layer by layer, which is beneficial for regulating the Fermi energy level and thus optimizing the carrier transport performance of the device; the electron transport layer, the hole transport layer, and the light absorption layer of the present invention are all quantum dot films composed of nanoparticles, and the material is more suitable for flexible devices; the use of ultrasonic spraying technology can reduce the waste of quantum dot raw materials, can realize the flexibility of the device, and has the application potential of low cost and large-scale production; the flexible interdigitated back-contact solar cell structure designed by the present invention has the advantage of high flexibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 It is a device structure diagram of the present invention.
[0011] Figure 2 Schematic diagram of the energy levels of the device of the present invention.
[0012] Figure 3 It is a transmission electron microscope (TEM) image of the CsPbI3 quantum dots prepared by the present invention.
[0013] Figure 4It is an ultraviolet-visible absorption spectrum (UV-VIS) diagram of the CsPbI3 quantum dot solution prepared by the present invention.
[0014] Figure 5 This is a scanning electron microscope (SEM) image of the CsPbI3 quantum dot flexible film prepared by the present invention. DETAILED DESCRIPTION
[0015] like Figure 1 As shown in the specific implementation manner of the present invention, the device includes: (1) a flexible substrate 1; (2) metal electrode layer 2; (3) Tin dioxide (SnO2) electron transport layer 3; (4) nickel oxide (NiO) hole transport layer 4; (5) CsPbI3 perovskite quantum dot light absorption layer 5; (6) Encapsulation film layer 6.
[0016] The specific preparation and preparation process of a photoconversion device based on all-inorganic perovskite quantum dots are as follows: After the polyethylene terephthalate flexible film substrate was purchased, it was treated with ultraviolet ozone for 10 minutes to obtain the polyethylene terephthalate flexible film flexible substrate 1.
[0017] Preparation of metal electrode layer 2: A metal electrode layer 2 is deposited on a polyethylene terephthalate flexible film flexible substrate 1 by sputtering using metallic silver. The metal electrode layer 2 is made into a finger electrode structure through a mask. The deposition thickness is 120 nm. The material is metallic silver. The finger width is 0.8 mm. The gap distance between adjacent fingers is 0.5 mm. The electrode layer is divided into a positive electrode region and a negative electrode region. The positive and negative electrode regions are arranged alternately at intervals. The metal electrode layer 2 is a periodic long strip pattern with finger-like cross arrangement.
[0018] Preparation of SnO2 electron transport layer 3: 15 wt % SnO2 dilution and deionized water are mixed and stirred in a volume ratio of 1:3 to prepare a SnO2 precursor solution for use. Then, a layer of SnO2 electron transport layer 3 is sprayed on the silver electrode layer 2 through a mask using an ultrasonic spraying method. The thickness is 40 nm, the annealing temperature is 150 ° C, and the annealing time is 30 min. During the spraying process, the position and shape of the electron transport layer are kept consistent with the negative electrode region of the metal electrode layer through the mask, which is an equidistantly arranged interdigitated long strip pattern. The process parameters of the ultrasonic spraying method are set as follows: the nozzle power is 1.5 W, the flow rate is 0.25 mL / min, the distance between the nozzle and the substrate is 60 mm, nitrogen is used as the carrier gas, and the gas pressure is 0.15 MPa.
[0019] Preparation of NiO hole transport layer 4: 0.05 mol of nickel nitrate hexahydrate Ni(NO3)2·6H2O powder was dissolved in deionized water to prepare nickel nitrate Ni(NO3)2 solution, and a 10 mol / L sodium hydroxide NaOH aqueous solution was mixed into the nickel nitrate Ni(NO3)2 solution until the pH value reached 10. The suspension was stirred evenly and then washed with deionized water to obtain nickel hydroxide Ni(OH)2 precipitate. The nickel hydroxide Ni(OH)2 precipitate was baked into powder and then calcined at 300°C for 1.5 h to obtain NiO powder. NiO powder was dissolved in deionized water and filtered as a precursor solution with a concentration of 0.9 mg / ml. Then, a NiO hole transport layer 4 was sprayed on the silver electrode layer 2 using an ultrasonic spraying method. The spraying thickness was 40 nm, the annealing temperature was 150 °C, and the annealing time was 30 min. During the spraying process, the position and shape of the hole transport layer were kept consistent with the positive electrode area of the metal electrode layer through a mask, which was an equidistantly arranged interdigitated strip pattern. The process parameters of the ultrasonic spraying method were set as follows: the nozzle power was 1.5 W, the flow rate was 0.25 mL / min, the distance between the nozzle and the substrate was 60 mm, nitrogen was used as the carrier gas, and the gas pressure was 0.15 MPa. During the spraying process, a mask was used for interval deposition so that a gap was left between adjacent interdigits to separate the SnO2 electron transport layer 3 and the NiO hole transport layer 4, and the gap distance was 0.5 mm.
[0020] Preparation of CsPbI3 perovskite quantum dot light absorbing layer 5: The synthesized CsPbI3 quantum dots were dispersed in n-octane to prepare a 20 mg / mL CsPbI3 quantum dot n-octane solution, and an ultrasonic spraying method was used to prepare a CsPbI3 quantum dot absorption layer 5 with a thickness of 80 nm on the electron transport layer 3 and the hole transport layer 4. The process parameters of the ultrasonic spraying method were set as follows: the nozzle power was 1.5 W, the flow rate was 0.25 mL / min, the distance between the nozzle and the substrate was 60 mm, nitrogen was used as the carrier gas, and the gas pressure was 0.15 MPa.
[0021] Preparation of encapsulation film layer 6: A pressure-sensitive encapsulation film is used, and the encapsulation film is fixed with a mold to completely cover the CsPbI3 perovskite quantum dot light-absorbing layer 5 with the encapsulation film. Finally, the mold is pressed to make the encapsulation film layer 6 and the CsPbI3 perovskite quantum dot light-absorbing layer 5 bonded without gaps. The device structure is as follows: Figure 1 shown.
Claims
1. A method for preparing an all-inorganic perovskite quantum dot flexible interdigitated back contact solar cell, characterized in that: The method comprises the following steps: (1) Preparing an interdigitated metal electrode layer on a polyethylene terephthalate flexible film; (2) preparing a tin dioxide electron transport layer in the negative electrode region of the interdigitated metal electrode layer by using ultrasonic spraying technology; (3) preparing a nickel oxide hole transport layer in the positive electrode region of the interdigitated metal electrode layer by using ultrasonic spraying technology; (4) preparing a perovskite quantum dot light absorbing layer on the electron transport layer and the hole transport layer by using ultrasonic spraying technology; (5) Preparing a pressure-sensitive encapsulation adhesive on the quantum dot light-absorbing layer.
2. The method for preparing the all-inorganic perovskite quantum dot flexible interdigitated back contact solar cell according to claim 1, characterized in that: In step (1), the preparation method of the interdigitated metal electrode layer is as follows: treating a polyethylene terephthalate flexible film with an ultraviolet ozone method for 10 min, and then sputtering depositing an interdigitated metal electrode layer on the polyethylene terephthalate flexible film, the deposition thickness is 100~150 nm, the material is metallic silver, the electrode layer is divided into a positive electrode region and a negative electrode region, the positive and negative electrode regions are alternately arranged, specifically presenting a periodic long strip pattern of finger-like cross arrangement, the interdigitated width is 0.5~2 mm, and the gap distance between adjacent interdigitated fingers is 0.2~1 mm.
3. The method for preparing the all-inorganic perovskite quantum dot flexible interdigitated back contact solar cell according to claim 1, characterized in that: In step (2), an electron transport layer is prepared in the negative electrode region of the interdigitated metal electrode layer by an ultrasonic spraying method. The electron transport layer material used is a diluted tin dioxide SnO2 aqueous solution, the spraying thickness is 30-50 nm, the annealing temperature is 100-150 °C, and the annealing time is 10-40 min. During the spraying process, a mask is used to ensure that the position and shape of the electron transport layer are consistent with the negative electrode region of the metal electrode layer, forming an equidistantly arranged interdigitated long strip pattern.
4. The method for preparing the all-inorganic perovskite quantum dot flexible interdigitated back contact solar cell according to claim 1, characterized in that: In step (2), the process parameters of the ultrasonic spraying method are set as follows: nozzle power is 1.5~3 W, flow rate is 0.1~0.5 mL / min, the distance between the nozzle and the substrate is 50~70 mm, the carrier gas is nitrogen, and the carrier gas pressure is 0.1~0.3 MPa.
5. The method for preparing the all-inorganic perovskite quantum dot flexible interdigitated back contact solar cell according to claim 1, characterized in that: In step (3), a hole transport layer is prepared in the positive electrode region of the interdigitated metal electrode layer by an ultrasonic spraying method. The hole transport layer material used is a diluted nickel oxide NiO aqueous solution with a concentration of 0.5-1 M, which is prepared at low temperature by nickel nitrate Ni(NO3)2 aqueous solution and sodium hydroxide NaOH aqueous solution. The spraying thickness is 30-50 nm, the annealing temperature is 150-200 °C, and the annealing time is 10-40 min. During the spraying process, a mask is used to ensure that the position and shape of the hole transport layer are consistent with the positive electrode region of the metal electrode layer, forming an equidistantly arranged interdigitated long strip pattern. During the spraying process, a mask is used for interval deposition so that gaps are left between adjacent interdigits to separate the electron transport layer and the hole transport layer, and the gap distance is 0.2-1 mm.
6. The method for preparing the all-inorganic perovskite quantum dot flexible interdigitated back contact solar cell according to claim 1, characterized in that: In step (3), the process parameters of the ultrasonic spraying method are set as follows: nozzle power is 1.5~3 W, flow rate is 0.1~0.5 mL / min, the distance between the nozzle and the substrate is 50~70 mm, the carrier gas is nitrogen, and the carrier gas pressure is 0.1~0.3 MPa.
7. The method for preparing an all-inorganic perovskite quantum dot flexible interdigitated back contact solar cell according to claim 1, characterized in that: In step (4), ultrasonic spraying is used to prepare the perovskite quantum dot light absorbing layer. The component of the perovskite quantum dot light absorbing layer is an octane solution of CsPbI3 quantum dots. The CsPbI3 quantum dots are prepared by hot injection method. The band gap is 1.7 eV, the concentration is 10-20 mg / mL, the size of the CsPbI3 quantum dots is 5-15 nm, and the spraying thickness is 60-100 nm. The CsPbI3 quantum dot film formed by spraying is dense and has no gaps.
8. The method for preparing the all-inorganic perovskite quantum dot flexible interdigitated back contact solar cell according to claim 1, characterized in that: In step (4), the process parameters of the ultrasonic spraying method are set as follows: nozzle power is 1.5~3 W, flow rate is 0.1~0.5 mL / min, the distance between the nozzle and the substrate is 50~70 mm, the carrier gas is nitrogen, and the carrier gas pressure is 0.1~0.3 MPa.
9. The method for preparing an all-inorganic perovskite quantum dot flexible interdigitated back contact solar cell according to claim 1, characterized in that: In step (5), packaging is performed using a pressure-sensitive packaging film.
Citation Information
Patent Citations
Parallel interdigital full-back contact perovskite solar cell and preparation method thereof
CN111312900A
Back contact perovskite silicon laminated cell assembly, preparation method thereof and solar cell
CN114203831A
Preparation method of all-inorganic perovskite quantum dot light conversion device
CN116504884A